Low-Field Magnetic Resonance Imaging Findings in 18 Dogs With Presumed Optic Neuritis - Muñiz Moris, Laura; Cherubini, Giunio Bruto; Caine, Abby (Frontiers in Veterinary Science, 2021)
Canine optic neuritis has been attributed to a focal or disseminated form of granulomatous meningoencephalitis (GME) amongst other etiologies. Magnetic resonance imaging (MRI) has been proven to help differentiate the structures within the optic nerve sheath and therefore could aid the diagnosis of optic neuritis in dogs. The objectives of this study were to describe and compare the MRI abnormalities affecting the optic nerve sheath complex and optic chiasm in dogs with clinically suspected optic neuritis as a component of meningoencephalitis of unknown etiology (MUE) or as an isolated form (I-ON). Retrospective evaluation of patient details, clinical signs, cerebrospinal fluid (CSF) analysis and MRI findings of dogs with clinically suspected optic neuritis between January 2011 and May 2018 was performed. Eighteen dogs met the inclusion criteria. MRI findings included contrast enhancement of both optic nerves (11/18) and optic chiasm (6/18), changes within the CSF volume surrounding the optic nerve (10/18), changes to the optic disc (10/18), changes of size or signal affecting the optic chiasm (10/18), changes in the Short TI inversion recovery (STIR) signal of the optic nerve (7/15), retrobulbar changes (3/18), and concurrent brain lesions (13/18). A variety of subtle MRI features may indicate optic nerve involvement and low-field MRI is a sensitive method to detect changes within the optic nerve sheath complex in dogs with optic neuritis as an isolated form (I-ON) or as an extension of MUE.